Descriptive assessment of conversational skills: Towards benchmarks for young adults with social deficits. Issue 3 (5th April 2021) - Hood, Stephanie A.; Beauchesne, Britany M.; Fahmie, Tara A.; Go, Alexandra
Abstract : Descriptive assessments are necessary to identify social norms and establish a foundation for experimental analysis. Much of the social skills intervention literature involves goals that have been selected through interviews and direct observation of behavior without a reference to desired outcomes. The purpose of the current study was to extend research on descriptive assessments of conversations by including additional measures and examining conversational behavior across contexts. We conducted a descriptive assessment of social skills exhibited by 16 neurotypical young adults. Participants had 10‐min conversations in groups and 1‐on‐1 with friends and novel individuals. We then assessed variability within and across participants on a wide array of relevant measures. Throughout the conversations, participants shared the conversation time equally, spent most of the conversation time making on‐topic comments, and gazed at their conversation partner more frequently while listening than while speaking. These descriptive data extend current research, inform future experimental analyses, and may guide clinical decisions.